1998
DOI: 10.2105/ajph.88.11.1715
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in reporting household gun ownership.

Abstract: OBJECTIVES: This study examined errors in estimating household gun ownership that result from interviewing only 1 adult per household. METHODS: Data from 2 recent telephone surveys and a series of in-person surveys were used to compare reports of household gun ownership by husbands and wives. RESULTS: In the telephone surveys, the rate of household gun ownership reported by husbands exceeded wives' reports by an average of 12 percentage points; husbands' reports also implied 43.3 million more guns. The median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 16 publications
6
64
0
Order By: Relevance
“…21,22,26,28,29 This conclusion was drawn from several studies that demonstrated that men and women from theoretically similar households report different prevalence of firearm-ownership and -storage practices. This study contributes to what is known by comparing responses from men and women from the same households.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…21,22,26,28,29 This conclusion was drawn from several studies that demonstrated that men and women from theoretically similar households report different prevalence of firearm-ownership and -storage practices. This study contributes to what is known by comparing responses from men and women from the same households.…”
Section: Discussionmentioning
confidence: 97%
“…More needs to be known about how couples make decisions about whether to have firearms in the home, as well as how to store them. That men are more likely to obtain, personally own, use, carry, and take care of firearms 26 suggests that men's reports are more likely to be accurate than their female partners; however, this may not be the case when women are the sole owners of firearms. Our research and that of others 19 suggests that some men do not disclose to their partners that there are guns in the home.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations